The Indigenous Counselling and Nicotine (ICAN) QUIT in Pregnancy Pilot Study protocol: a feasibility step-wedge cluster randomised trial to improve health providers' management of smoking during pregnancy. Issue 8 (4th August 2017) - Bar-Zeev, Yael; Bonevski, Billie; Bovill, Michelle; Gruppetta, Maree; Oldmeadow, Chris; Palazzi, Kerrin; Atkins, Lou; Reath, Jennifer; Gould, Gillian S
Abstract : Introduction: Indigenous women have the highest smoking prevalence during pregnancy (47%) in Australia. Health professionals report lack of knowledge, skills and confidence to effectively manage smoking among pregnant women in general. We developed a behaviour change intervention aimed to improve health professionals' management of smoking in Indigenous pregnant women—the Indigenous Counselling And Nicotine (ICAN) QUIT in Pregnancy. This intervention includes webinar training for health professionals, an educational resources package for health professionals and pregnant women, free oral nicotine replacement therapy (NRT) for pregnant women, and audit and feedback on health professionals' performance. The aim of this study is to test the feasibility and acceptability of the ICAN QUIT in Pregnancy intervention to improve health professionals' provision of evidence-based culturally responsive smoking cessation care to Australian Indigenous pregnant smokers. Methods and analysis: This protocol describes the design of a step-wedge cluster randomised pilot study. Six Aboriginal Medical Services (AMSs) are randomised into three clusters. Clusters receive the intervention staggered by 1 month. Health professionals report on their knowledge and skills pretraining and post-training and at the end of the study. Pregnant women are recruited and followed up for 3 months. The primary outcome is the recruitment rate of pregnant women. Secondary outcomes include feasibility of recruitment and follow-up of participating women, and webinar training of health professionals, measured using a designated log; and measures of effectiveness outcomes, including quit rates and NRT prescription rates. Ethics and dissemination: In accordance with the Aboriginal Health and Medical Research Council guidelines, this study has been developed in collaboration with a Stakeholder and Consumer Aboriginal Advisory Panel (SCAAP). The SCAAP provides cultural consultation, advice and direction to ensure that implementation is acceptable and respectful to the Aboriginal communities involved. Results will be disseminated to AMSs, Aboriginal communities and national Aboriginal bodies. Registration details: This protocol (version 4, 14 October 2016) is registered with the Australian and New Zealand Clinical Trials Registry (Ref #: ACTRN12616001603404).